Abu al-Barakat al-Baghdadi (467-547H): Suatu Biografi - Wan Abdullah, Wan Suhaimi (Jurnal Usuluddin, 1999)
The article deals with Abu al-Barakat al-Baghdadi’s life and works. It attempts to give a complete biography of the figure, as one of the great critique thinker in the history of the Islamic Philosophy.